PENGARUH KUALITAS LAYANAN KESEHATAN, FASILITAS KESEHATAN, DAN LAYANAN PERAWAT TERHADAP KEPUASAN PASIEN RAWAT JALAN DI PUSKESMAS RANTAU PANJANG, MERANGIN, JAMBI [THE INFLUENCE OF HEALTHCARE SERVICE QUALITY, HEALTH FACILITIES, AND NURSES' SERVICES ON THE SATISFACTION OF OUTPATIENTS AT PUSKESMAS RANTAU PANJANG, MERANGIN, JAMBI] - Mayrawati, Nora; Saepudin, Didin; Syahidin, Rukhiyat (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
This study aims to examine the influence of healthcare service quality, healthcare facilities, and nursing care on outpatient satisfaction at Puskesmas Rantau Panjang, Merangin, Jambi. A quantitative approach was employed using Partial Least Squares (PLS) to analyze the relationships among the variables. The sample consisted of 98 respondents selected through purposive sampling, with questionnaires distributed to outpatients based on inclusion criteria. The results indicate that healthcare service quality is perceived as fairly good, healthcare facilities are categorized as good, and nursing care is considered fairly good. Partially, healthcare service quality and healthcare facilities significantly affect patient satisfaction, whereas nursing care does not show a significant effect. However, when examined simultaneously, the three exogenous variables collectively demonstrate a significant impact on outpatient satisfaction, with an R-square value of 0.62, suggesting that 62% of the variation in patient satisfaction can be explained by these variables. The study concludes that enhancing healthcare service quality and providing adequate facilities are key determinants of patient satisfaction. The findings carry managerial implications, emphasizing that Puskesmas management should prioritize improving service quality and upgrading facilities to enhance overall patient satisfaction